Future-oriented science learning and its effects on students’ emotions, futures literacy and agency in the Anthropocene - Chan, J; Erduran, S (Springer, 2024)
Science education bears the broader objective of nurturing students today to be scientifically-literate citizens of tomorrow who are able to foresee challenges, invent solutions and make responsible decisions for global issues. As a prelude to the new focus of agency in the Anthropocene, this paper presents an intervention on climate change with upper secondary students in a museum of natural history in England. Instructional strategies such as infusing scenarios and arts into scientific discussions were adopted to induce imagination, future-oriented thinking and emotional responses. Statistical results showed that the intervention significantly enhanced participants’ futures literacy, environmental agency and positive emotions. However, it did not increase their interests in learning science in out-of-school context. Implications of this study will shed light on futurising science and climate education in research and practice.